Implementation of Innovations Gigades.id in Teberau Panjang, Kuantan Singingi Regency - Diki Zulkarnain; Dedi Kusuma Habibie (Jurnal Magister Administrasi Publik, 2022)
One of strategy to create effective and efficient public services is to innovate in providing services to the public. The application of Gigades.id is a form of public service innovation. This application is made and managed by a private sector, namely PT. Phoenix based in Kuantan Singingi Regency. The Gigades.id application is used to provide digital public services to rural society. To implement the innovation of Gigades.id application in rural areas, PT. Phoenix builds synergy or cooperation with the local government. This study use innovation theories by Rogers that has 5 (five) innovation implementation indicators, namely relative advantage, compatibility, complexity, trialability, and observability. The type of research used in this study is qualitative research with a descriptive approach. The required data collection, both primary data and secondary data from interviews, observations, documentation, is then analyzed so that conclusions can be drawn from the research problem. The findings of this study are that the implementation of innovation has been running according to the indicators of innovation proposed by Rogers, eventhough in the process of implementation the innovation still not maximal. Abstacle factors the implementation of Gigades.id are the quality of the internet network, socialization, and human resources.